Distribution and abundance of arthropod species in pasture communities of three Azorean islands (Santa Maria, Terceira and Pico) - Borges, Paulo A. V. (2009)
This work provides evidence that the "hollow curve" is a consistent pattern in the range size distribution of taxonomic and ecological groups of arthropod pasture dwelling species. Many of the inconsistent results relating range size to herbivores diet breadth are probably due to historical constraints in the colonization of the islands and particular characteristics of the habitats studied (e.g. types of resources available). The positive relationship between range size and abundance may be explained by the "resource usage model". However, the slope of the regression line relating distribution to abundance was similar for different groups which suggests there is no difference in the way that the species’ local abundance scales with distribution in the four assemblages of species studied and that there is a close relationship between the trophic groups studied. This suggests that the “resource availability model” could be the explanation for the distribution and abundance of pasture spider and insect species. More work needs to be conducted in order to evaluate the relationship between diet breadth, habitat specialization and range size in the islands.